Three sisters, three queens [compact disc, unabridged] - Gregory, Philippa (Simon & Schuster Audio, 2016)
When Katherine of Aragon is brought to the Tudor court as a young bride, the oldest princess, Margaret takes her measure. With one look, each knows the other for a rival, an ally, a pawn, destined with Margaret's younger sister Mary to a sisterhood unique in the world. The three sisters will become the queens of England, Scotland, and France. United by family loyalties and affections, the three queens find themselves set against each other. Through betrayals, dangers, loss, and passion, they find the only constant in their lives is their special bond, more powerful than any man, even a king.